2017
DOI: 10.1190/tle36040330.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic interpretation below tuning with multiattribute analysis

Abstract: The tuning-bed thickness or vertical resolution of seismic data traditionally is based on the frequency content of the data and the associated wavelet. Seismic interpretation of thin beds routinely involves estimation of tuning thickness and the subsequent scaling of amplitude or inversion information below tuning. These traditional below-tuning-thickness estimation approaches have limitations and require assumptions that limit accuracy. The below-tuning effects are a result of the interference of wavelets, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Several utilizations of unsupervised learning are clustering, dimensionality reduction, and anomaly detection. In the geosciences field of study, unsupervised learning has been applied to aid interpretation, such as multi-attribute analysis [6][7][8]16], AVO cross-plotting, and classification [3,17].…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Several utilizations of unsupervised learning are clustering, dimensionality reduction, and anomaly detection. In the geosciences field of study, unsupervised learning has been applied to aid interpretation, such as multi-attribute analysis [6][7][8]16], AVO cross-plotting, and classification [3,17].…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Recent studies have shown promising applications of machine learning techniques to reflection seismic data to aid in the interpretation of geologic patterns [8][9][10][11]. Some of these applications are at the sub-seismic resolution scale since machine learning works on a sample interval basis, as opposed to being limited by the seismic wavelet [8,12].…”
Section: Figurementioning
confidence: 99%
“…Flexer 52 discussed the application of SOM for clustering and data visualization. Roden et al, 53 implemented SOM to analyze several seismic attributes to identify natural patterns for stratigraphic interpretation. Meanwhile, Köhler et al 54 used SOMs to detect and classify events in continuous seismic wavefield records also the SOM was able to visualize the 24-hour human activity cycle.…”
Section: Self-organizing Map Clustering (Som)mentioning
confidence: 99%